QUALITATIVE INDICATORS OF LUBRICANT MATERIAL OBTAINED BASED ON GOSSYPOLO RESIN (Scientific journal of the Fergana State University, 2024)
A mixture of lubricant was obtained by thermal distillation of gossypol resin in a cylindrical reactor. In order to improve the quality of the lubricant, the additive lithium hydroxide was used and 6 samples of the lubricant were obtained. Each sample of the resulting lubricant was tested by determining the pour point and flash point in an open crucible. According to the obtained indicators of the viscosity index and pour point, sample SM-4 has the best performance than other samples of the lubricant. But in terms of flash point, samples SM-2 and SM-4 have higher indicators than other samples of lubricant. Based on the results obtained, samples SM-2 and SM-4 of the lubricant are recommended to be used as a lubricant for high-speed rotating equipment.